Sticky Fibrin Adhesion: Enlightenment from a Case of Tuberculous Pleurisy - Yanti, Budi; Bakhtiar, Bakhtiar; Azizi, Jamalul (Faculty of Medicine Universitas Airlangga, 2024)
Introduction: Tuberculous pleurisy (TP) is the pleural inflammation caused by Mycobacterium tuberculosis (MTB) and a rare manifestation of childhood tuberculosis (TB). It is characterized by a large amount of fibrin, sticky adhesion, and even calcification. Pleural adhesion can significantly affect respiratory function and quality of life. Therefore, early detection, prompt therapy, and drainage of pleural effusion are crucial for preventing pleural adhesion. This case report is intended to enhance clinician awareness regarding avoiding and managing pleural thickening in TP. Case: A 14-year-old child had shortness of breath, fever for 2 weeks, cough, loss of appetite, and no smoking history. The laboratory results showed anemia and non-reactive human immunodeficiency viruses (HIV), analyzed pleural fluid monocyte showed 72%, and glucose 58%. Adenosine deaminase (ADA) analysis showed a rise above 61 U/L. The tuberculin skin test was negative. The chest X-ray showed right pleural effusion, the chest ultrasonography revealed a right hemithorax echo-free plane, and the computed tomography (CT) scan showed right pleural effusion and pulmonary fibrosis. The thoracoscopy view showed fibrinous adhesion-producing tenting and vascularization in the base without multiple nodules. Water-sealed drainage was performed and produced approximately 3,450 ml with serous xanthochromia. Then the patient was diagnosed with TP and treated with anti-TB drugs and steroids. Conclusion: Typical TP with fibrinous adhesions is an infrequent condition. This case report highlighted the importance of extensive screening using a thoracoscopy view and ADA analysis in patients with TP, especially in countries with a high TB burden.